- Perbandingan Pengaturan dan Implementasi Doktrin Fiduciary Duty di Indonesia dan Singapura: - - Alya Nabita Az-zahra; Sri Bakti Yunari (Faculty of Law, Universitas Trisakti, 2024)
The doctrine of fiduciary duty is a modern doctrine of Limited Liability Companies regulated in Law Number 40 of 2007 concerning Limited Liability Companies, hereinafter referred to as UUPT. Meanwhile in Singapore, Fiduciary Duty is regulated in the Singapore Companies Act, hereinafter referred to as SCA. The main problem of this research is how the fiduciary duty doctrine is regulated in Indonesia and Singapore and how the fiduciary duty doctrine is implemented in Indonesia and Singapore. The type of research used is normative research, descriptive research, secondary data, qualitative analysis, deductive conclusion drawing. Based on the analysis, there are similarities and differences in UUPT and SCA. It is hoped that in future, the fiduciary duty doctrine should be regulated clearly and in detail in the UUPT and SCA.